The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.4034/pboci.2017.171.37
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Toothache in Patients Affected by Hereditary Coagulopathies

Abstract: Objective: To determine a probabilistic model that represents the likelihood of the event Dental Pain to occur in Brazilians patients affected by hereditary coagulopathies. Material and Methods: In this cross-sectional study, information on use and access to dental services, oral morbidity, self-perceived oral health and behavioral health habits were obtained through semi-structured questionnaire and analyzed by means of logistic regression. Results: High prevalence of dental caries was observed for children a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Pakistan [12], India [6,10,14,[32][33][34], Northern Ireland [9], Brazil [15,[35][36][37], Uruguay [18], Romania [13],…”
Section: Studies Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pakistan [12], India [6,10,14,[32][33][34], Northern Ireland [9], Brazil [15,[35][36][37], Uruguay [18], Romania [13],…”
Section: Studies Characteristicsmentioning
confidence: 99%
“…Only six studies reported a calibration process [4,12,15,31,35,36]. Regarding the eligibility criteria, nine studies excluded other systemic or blood diseases [10,31,32,34,37], and HIV-positive children [20]. No study reported the rate of non-response.…”
Section: Quality Assessmentmentioning
confidence: 99%
“…Dental pain is evaluated varied instruments: Dental Pain Questionnaire [13], Oral Health Impact Profile [14] and others. Dental pain is associated with worse socioeconomic status [15] and it is one of the most frequent dental discomforts [16].…”
Section: Introductionmentioning
confidence: 99%